Lessons learned and potential long-term effects on athletic trainers and clinical practice after a global pandemic - Madden, M.; Kneavel, M. E.; Bowman, T. G. (Journal of Athletic Training, 2022)
Context Perceived stress and burnout are significant concerns among athletic trainers (ATs) due to growing professional demands. The global COVID-19 pandemic brought additional stressors, especially for health care providers, including the need to learn and integrate new skill sets in order to continue providing safe and effective patient care.